DOPAMINE EFFECT ON CARDIAC REMODELING IN EXPERIMENT - V. R. Veber; M. P. Rubanova; S. V. Zhmailova; P. M. Gubskaya; I. A. Suchenko; V. E. Goricina; T. M. Nurjanova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study morphologic changes in myocardium of Wistar rats caused by single and long term dopamine administration. Methods. In acute study dopamine 10 mkg/kg was administrated to 15 rats by a single intraperitoneal injection. The material was taken in 2, 6, 24 hours and in 1 month after drug administration. In chronic study dopamine 10 mkg/kg was administrated to 15 rats 3 times a day by intraperitoneal injections during 2 weeks. The material was taken just after the drug administration was stopped and in 1 month of animals keeping without stress and drug influences. Control group included 15 rats comparable with experimental animals in age and weight. They were keeped without stress and drug influences. Morphometric parameters of left and right ventricles were evaluated as well as density of cardiomyocytes, collagen, vessels and volume of extracellular space. Results. The enlargement of cardiac fibrosis is found both in acute, and in chronic study. In acute study cardiac fibrosis was located mainly in a right ventricle. In chronic study cardiac fibrosis was located in both ventricles, but also mainly in a right one. Conclusion. Significant morphological «asynchronism» of the left and right ventricles remodeling requires elaboration of methods of myocardium protection and cardiac function control during dopamine administration.